Analyzing components of community-based tourism development in rural areas; case of Marivan and Sarvabad counties - Hojjat Varmazyari; Marzye Fathi; khalil kalantari; Muhammad Asef Shaiq (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2023)
Rural tourism as a global industry has been considered an effective solution for rural development. One of the most important issues in rural tourism is that it is community-based. Community-based tourism aims to create economic benefits and improve the quality of life for the local communities. The first and most important principle in community-based tourism is the participation of all stakeholders in the planning and development process. However, in developing countries, its realization has been faced with problems. This research was conducted to analyze the components of community-based rural tourism development in Marivan and Sarvabad cities.Materials and Methods The statistical population was the villagers over 15 years old (women and men, marginal strata, and local elites) in the villages with high potential for tourism in Marivan and Sarvabad Counties of Kurdistan province. A survey method was used to collect information. The data collection tool was a researcher-made questionnaire. In addition to dispersion and centrality statistics, inferential tests of mean comparison and exploratory factor analysis were used to analyze the data.Discussion and ResultsFrom the point of view of different strata of rural society, the most important component of community-based rural tourism development is "inclusiveness and horizontal networking. " In this regard, facilitators and governmental and non-governmental agents of rural tourism should consider a suitable mechanism to strengthen the dialogue and exchange of opinions between the representatives of different sections of the villagers, the participation of the poor sections in the decision-making and planning process, and the division of social responsibilities among the villagers. "Empowerment and strengthening of infrastructures" are the second component that can be effective in developing community-based tourism, especially by creating a sense of collective identity among villagers and education and raising awareness. "Open and demand-oriented innovation" has been the third effective component in developing community-based tourism. In this regard, it is emphasized to use the advice and help of external experts and produce local products based on market needs. The fourth component, "preserving local authenticity," is another important component in developing community-based rural tourism. Strengthening the sense of belonging and employing villagers will preserve and strengthen cultural authenticity and realize the community-based approach. The last extracted component emphasizes profit and fair participation as a condition for realizing the community-based approach in rural tourism development.ConclusionThis study can play a major role in providing correct insight to the authorities on promoting local communities’ participation in the tourism industry and their benefits. Among the solutions that are suggested concerning the topic of the present study is the emphasis on the development of low-cost rural tourism projects, which by providing the gradual and successful entry of marginalized groups into the process of planning and development of rural tourism at the end, lead to the empowerment of the people experiencing poverty and the use of the high potential of rural women.